2022
DOI: 10.1155/2022/2091615
|View full text |Cite
|
Sign up to set email alerts
|

Cebpb Regulates Skeletal Stem Cell Osteogenic Differentiation and Fracture Healing via the WNT/β-Catenin Pathway

Abstract: Fracture is the most common traumatic organ injury, and fracture nonunion is a critical clinical challenge. The research on the mechanisms of skeletal stem cell (SSC) differentiation and fracture healing may help develop new treatment strategies and improve the prognosis of patients at high risk of nonunion. Bioinformatic analysis of scRNA-seq data of mouse SSCs and mouse osteoprogenitors was applied to discover major transcription factors for the regulation of SSC differentiation. FACS was used to isolate SSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the pancreas, GATA6 binds the promoter of the digestive enzyme genes Rbpjl and Mist1 facilitating acinar differentiation 44 . Similarly, Cebp3 is also involved in cell development and differentiation, and a previous study has shown that it can regulate osteoblasts differentiation through the WNT/ β‐Catenin pathway 45 . Follicular development is a step‐by‐step orchestrated process containing the programmed expression of gonadal hormones and other environmental factors, 5,31 which probably affected the activity of these TFs and thus regulates cumulus transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pancreas, GATA6 binds the promoter of the digestive enzyme genes Rbpjl and Mist1 facilitating acinar differentiation 44 . Similarly, Cebp3 is also involved in cell development and differentiation, and a previous study has shown that it can regulate osteoblasts differentiation through the WNT/ β‐Catenin pathway 45 . Follicular development is a step‐by‐step orchestrated process containing the programmed expression of gonadal hormones and other environmental factors, 5,31 which probably affected the activity of these TFs and thus regulates cumulus transition.…”
Section: Resultsmentioning
confidence: 99%
“… 44 Similarly, Cebp3 is also involved in cell development and differentiation, and a previous study has shown that it can regulate osteoblasts differentiation through the WNT/ β‐Catenin pathway. 45 Follicular development is a step‐by‐step orchestrated process containing the programmed expression of gonadal hormones and other environmental factors, 5 , 31 which probably affected the activity of these TFs and thus regulates cumulus transition. In total, our findings revealed the stage‐specific transcriptional programs underlying cumulus transition in rat ovaries.…”
Section: Resultsmentioning
confidence: 99%